Phonological Development in 3–6-Year-Old Mandarin-Speaking Children with Autism, Developmental Delays, and Typical Development. - Liu, Min; Han, Jinhe; Zhang, Yuexin; Wen, Jieling; Wang, Yanxia; Hu, Xinyu; Sun, Mudi; Qu, Lu; Han, Xuling; Xu, Lian; Zhao, Hang; Lu, Haidan; et al. (Journal of Autism & Developmental Disorders, 2025)
Research on the phonological development of children with autism spectrum disorder (ASD) has not yet reached consistent conclusions, and systematic studies from different language groups are needed. This study aimed to systematically investigate the characteristics of phonological development in 3–6 year-old Mandarin-speaking children with ASD. We analyzed 10 min speech samples from 21 children with ASD, 18 development level-matched children with developmental disorders (DD), and 15 chronological age-matched typically developing (TD) children during semi-structured parent–child free play based on Mandarin phonological features. The children with ASD had a significantly smaller inventory than those with TD on the initial and final inventories. The children with ASD had only a significantly smaller initial inventory than those with DD in Phases 2 and 4. Compared with TD children, children with ASD used a higher proportion of V1 and V1V2C and a smaller proportion of V1V2V3, CV1C, and CV1V2C. No significant differences existed between ASD and DD children in the proportion of any syllable structure, but V1V2V3, CV1, and CV1V2C numbers were significantly fewer than in DD children. Children with ASD were significantly greater than children with TD in the diversity of V1V2, CV1, and overall syllables. ASD children had significantly fewer different types of syllables in both V1V2C and CV1 than did DD children and significantly greater diversity in CV1 and overall syllables than did DD children. These preliminary data suggest that the gap between TD and ASD children's language abilities increased with age, and this gap was reflected in initial, final, and syllable complexity and diversity. Children with DD and ASD showed similar language abilities, and children with DD showed detailed differences from those with ASD regarding initial, syllable complexity and diversity.